2020
DOI: 10.33545/gynae.2020.v4.i2a.503
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thrombocytopenia during pregnancy, and its effect on pregnancy and perinatal outcome

Abstract: Background: To study the prevalence of thrombocytopenia during pregnancy, its etiology and maternal and perinatal outcome. Methods: It was a prospective one year study of pregnancy with thrombocytopenia. The prevalence and cause of thrombocytopenia during pregnancy and its effect on maternal and perinatal outcome was studied. Result: Among 990 deliveries, 104 women were having thrombocytopenia during pregnancy. The commonest etiology was gestational thrombocytopenia (61.53%). Fetal complications were still bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Thrombocytopenia is a substantial hematological abnormality among pregnant women, affecting approximately 7–11% of pregnant women around the world. 1 , 2 Developing countries share a huge burden of thrombocytopenia. A study revealed 8.4% of the overall global burden of thrombocytopenia among pregnant women; with the highest burden reported from Africa (15.3%) and the lowest from Taiwan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombocytopenia is a substantial hematological abnormality among pregnant women, affecting approximately 7–11% of pregnant women around the world. 1 , 2 Developing countries share a huge burden of thrombocytopenia. A study revealed 8.4% of the overall global burden of thrombocytopenia among pregnant women; with the highest burden reported from Africa (15.3%) and the lowest from Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia is a common problem during pregnancy and is associated with several negative consequences such as excessive bleeding during or after childbirth, maternal and fetal complications, 10 , 13 which may result in significant morbidity and mortality for both mother and fetus. 3 , 14 Several epidemiological studies reported 19%, 15.8%, and 8.8–10.5% burden of thrombocytopenia among pregnant women in Libya, 9 Uganda, 15 and India, 2 , 16 , 17 respectively. Furthermore, the risk of bleeding was significantly higher among severe thrombocytopenic women, 15 , 18 which requires appropriate monitoring and management.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet count was done in the central square of the Neubauer chamber (1 central and four corner squares) and calculated by using the following formula. 14 Platelet count per liter=No of cells counted x dilution x 10 6 /Volume counted (ml).…”
Section: Methodsmentioning
confidence: 99%
“…Platelet counts of less than 100,000 per millilitre (ml), between 50,000 and 100,000 ml (ml), and less than 50,000 ml (ml) are considered mild, moderate, and severe, respectively, according to [3] research. [4] Approximately 7-11% of pregnant women throughout the world experience thrombocytopenia [5,6], making it a significant haematological disorder. Thrombocytopenia is disproportionately prevalent in low-income regions.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Multiple epidemiological studies found that thrombocytopenia was a major problem among pregnant women in Libya [12] (19%), Uganda [13] (15.8%), and India (8.8-10.5%). [6,14,15] The prevalence of thrombocytopenia during pregnancy is notably different in our demographic, and this study helps to determine the extent to which it is inadequately diagnosed and mismanaged in pregnant women. Obstetricians can benefit from the magnitude that has been documented.…”
Section: Introductionmentioning
confidence: 99%